The Effect of Patient Cost Sharing on Utilization, Health, and Risk Protection - Shigeoka, Hitoshi (American Economic Review, 2014)
This paper exploits a sharp reduction in patient cost sharing at age 70 in Japan, using a regression discontinuity design to examine its effect on utilization, health, and financial risk arising from out-of-pocket expenditures. Due to the national policy, cost sharing is 60–80 percent lower at age 70 than at age 69. I find that both outpatient and inpatient care are price sensitive among the elderly. While I find little impact on mortality and other health outcomes, the results show that reduced cost sharing is associated with lower out-of-pocket expenditures, especially at the right tail of the distribution. (JEL G22, I11, I12, I13, I18, J14)